A characterization of the external lines of a quadric cone in PG(3, q), q odd. Issue 8 (17th November 2017) - Vasarelli, Paolo
Abstract: In this article, the lines not meeting a quadric cone in PG (3, q ), q odd, are characterized by their intersection properties with points and planes.